2019
DOI: 10.1007/s00223-019-00591-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Vitamin D Deficiency to Limit Exacerbations in Respiratory Diseases: Utopia or Strategy With Potential?

Abstract: Patients with respiratory diseases such as cystic fibrosis, chronic obstructive pulmonary disease, or asthma often experience an acute worsening of respiratory symptoms, termed exacerbations. Although the course of exacerbations is disease specific, they are mostly triggered by a respiratory infection. Exacerbations often require hospitalization and are an important cause of mortality. Treatments of exacerbations aim to minimize the negative impact and to prevent subsequent events. Despite many existing therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 120 publications
(145 reference statements)
2
32
0
1
Order By: Relevance
“…These include the role of renin-angiotensin pathways in viral entry into alveolar cells and subsequent acute lung injury, dysregulated immune responses and activation of coagulation pathways (Quesada-Gomez et al, 2020). Interestingly, our literature review identified a number of studies/reviews (n = 24) providing some insight into the mechanistic explanations for the observed epidemiological relationship between vitamin D deficiency and increased risk/severity of respiratory infections (Ginde et al, 2009;Laaksi, 2012;Pfeffer and Hawrylowicz, 2012;He et al, 2013;Parekh et al, 2013;Lambert et al, 2014;Dancer et al, 2015;Greiller and Martineau, 2015;Vargas Buonfiglio et al, 2017;Xu et al, 2017;Jolliffe et al, 2018;Miraglia Del Giudice et al, 2018;Iyer and Bansal, 2019;Aygun, 2020;Brenner et al, 2020;Carter et al, 2020;Jakovac, 2020;Kakodkar et al, 2020;Maes et al, 2020;McCartney and Byrne, 2020;Misra et al, 2020;Molloy and Murphy, 2020;Panarese and Shahini, 2020;Quesada-Gomez et al, 2020;Tian and Rong, 2020;Zheng et al, 2020). Studies and narrative reviews suggest that entry of SARS-CoV-2 infection into alveolar epithelial cells, triggered by binding of the virus surface spike (S)-protein to the angiotensin converting enzyme 2 (ACE2) receptor, may lead to dysregulation of the renin-angiotensin system (RAS) resulting in acute lung injury due to toxic overaccumulation of angiotensin II (Ang II) in alveolar cells (Pfeffer and Hawrylowicz, 2012;Arnold, 2020;Carter et al, 2020;Jakovac, 2020;Kakodkar et al, 2020;Misra et al, 2020;…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the role of renin-angiotensin pathways in viral entry into alveolar cells and subsequent acute lung injury, dysregulated immune responses and activation of coagulation pathways (Quesada-Gomez et al, 2020). Interestingly, our literature review identified a number of studies/reviews (n = 24) providing some insight into the mechanistic explanations for the observed epidemiological relationship between vitamin D deficiency and increased risk/severity of respiratory infections (Ginde et al, 2009;Laaksi, 2012;Pfeffer and Hawrylowicz, 2012;He et al, 2013;Parekh et al, 2013;Lambert et al, 2014;Dancer et al, 2015;Greiller and Martineau, 2015;Vargas Buonfiglio et al, 2017;Xu et al, 2017;Jolliffe et al, 2018;Miraglia Del Giudice et al, 2018;Iyer and Bansal, 2019;Aygun, 2020;Brenner et al, 2020;Carter et al, 2020;Jakovac, 2020;Kakodkar et al, 2020;Maes et al, 2020;McCartney and Byrne, 2020;Misra et al, 2020;Molloy and Murphy, 2020;Panarese and Shahini, 2020;Quesada-Gomez et al, 2020;Tian and Rong, 2020;Zheng et al, 2020). Studies and narrative reviews suggest that entry of SARS-CoV-2 infection into alveolar epithelial cells, triggered by binding of the virus surface spike (S)-protein to the angiotensin converting enzyme 2 (ACE2) receptor, may lead to dysregulation of the renin-angiotensin system (RAS) resulting in acute lung injury due to toxic overaccumulation of angiotensin II (Ang II) in alveolar cells (Pfeffer and Hawrylowicz, 2012;Arnold, 2020;Carter et al, 2020;Jakovac, 2020;Kakodkar et al, 2020;Misra et al, 2020;…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulated immune responses associated with excessive and prolonged cytokine/chemokine responses known as a 'cytokine storm' , seem to be directly related to worse outcomes in COVID-19 (Carter et al, 2020;Slominski et al, 2020;Tian and Rong, 2020). All cells of the immune system have been shown to express the VDR, including T cells, and literature suggests that it is now well accepted that 1,25(OH)2D and vitamin D are important immune system regulators (Laaksi, 2012;Parekh et al, 2013;Greiller and Martineau, 2015;Miraglia Del Giudice et al, 2018;Iyer and Bansal, 2019;Maes et al, 2020;Misra et al, 2020;Tian and Rong, 2020). Vitamin D has been linked to innate immunity through identification of the cationic antimicrobial peptide cathelicidin as a vitamin D target gene and VDR upregulation in monocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, it will be a major challenge for future research to clearly discriminate between the baseline vitamin D status and its effects on the future course of the disease, including exacerbations, and COPD-mediated effects on 25-OHD levels, which in turn will then affect the disease. The question of vitamin D supplementation in COPD remains and several studies have indeed suggested a high potential to interfere with disease progression (51)(52)(53). Nevertheless, conflicting results have been obtained, up to now there is no explicit benefit for vitamin D supplementation in COPD and there are also caveats in vitamin D supplementation (19,54).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic questions remain whether vitamin D could and should be used to treat inflammatory arthritis, how it might work and who might benefit most? Complementing the theme of inflammation, Maes et al look at the impact of vitamin D on infection in pulmonary disease [13]. They present epidemiological evidence of vitamin D deficiency in chronic lung disease and the therapeutic effects of vitamin D. They also suggest therapeutic mechanisms for which readers may find Fig.…”
mentioning
confidence: 99%